Mucopolysaccharidosis Type I (Hurler – Scheie Syndrome): Case Report - Nato D. Vashakmadze; Olga I. Gumenuyk; Yuri V. Chernenkov; Ekaterina Yu. Zacharova; Igor A. Glushakov (Вопросы современной педиатрии)
Background. Mucopolysaccharidosis type I (MPS I) is an inherited disease caused by pathogenic variants in the IDUA gene, which encodes the lysosomal enzyme alpha-L-iduronidase. This clinical case demonstrates the importance of diagnosing rare diseases when patients have phenotypic features indicating hereditary pathology presence. Phenotype changes can be so-called “red flag” that helps specialists suspect and diagnose lysosomal storage diseases. Clinical case description. The patient was observed with delayed psychomotor development; she also had hepatomegaly and on auscultation of the heart there was a functional systolic murmur above the apex and in the Botkin–Erb point on heart auscultation. Coarse “garholoid” facial features attracted attention at external examination: large nose, wide sunken nose bridge, macroglossia, thick lips, synophrysis, scaphocephaly, wide chest, and flat-valgus feet. Echocardiography has revealed mitral valve insufficiency and hardened valve leaflets. Ophthalmologist examination: hypermetropic astigmatism. Psychiatrist examination: mental and speech development delay. Enzymatic diagnostics: significant decrease in alpha-Liduronidase activity. No further examinations were carried out due to the onset of the COVID-19 epidemic and parents' doubts about the diagnosis. The patient was readmitted to the hospital at the age of 6 years due to aggravation of her condition. A molecular genetic study has revealed two pathogenic variants in the IDUA gene. Diagnosis of MPS I was established according to the clinical data, results of biochemical and molecular genetic studies. Conclusion. This clinical case demonstrates the classic course of MPS I with typical phenotypic signs and lesions in various organs and systems. The presented case demonstrates the importance of professional vigilance among doctors of various specialties regarding orphan diseases.